Models of care for chronic myeloid leukemia patients during the COVID‐19 pandemic in the United Kingdom: Changes in patient attitudes to remote consultations and future implications. Issue 3 (14th May 2021) - Duncan, Nicholas; Deekes, Nigel; FitzGerald, David; Ng, Tin Wai Terry; Raghavan, Manoj
Abstract: The ongoing COVID‐19 pandemic has presented numerous challenges to the provision of patient care within hematology. We undertook a questionnaire‐based study investigating the experiences and opinions of patients with chronic myeloid leukemia (CML) in the UK in relation to the different models of follow‐up care received during the pandemic. One hundred fifty‐four patients completed the online questionnaire. Only 19% of patients had experienced remote clinics prior to the pandemic compared with 91% afterward. After having experience of remote clinics, the proportion of patients who were positive about the remote clinic concept increased from 34% to 52% (P < .05). However, when asked to compare their experiences with face to face versus remote clinics, 48% preferred face‐to‐face clinics compared with 17% preferring remote clinics (35% expressed no preference). During the pandemic, frequency of blood tests was unchanged for 71% of patients, although they were performed in a number of different locations. The majority of patients (57%) had medication delivered to their home, with a small number (8%) having difficulty obtaining their medication. In terms of future models of care, 72% of patients were in favor of building remote appointments into the clinic model with 61% expressing a preference for a mixture of remote and face‐to‐face appointments. There was also interest in greater utilization of primary care for blood testing. Our findings should help optimize future models of care for CML patients.